Gumprecht shadows: when to use this terminology? - Luci Maria Sant'Ana Dusse; Tamiris Paula Silva; Letícia Gonçalves Freitas; Lauro Mello Vieira; Adriano de Paula Sabino; Maria das Graças Carvalho (Sociedade Brasileira de Patologia Clínica, 2013)
The expression Gumprecht shadows historically refers to lymphocyte lysates commonly observed in patients with chronic lymphocytic leukemia (CLL). A literature review revealed that this term is restricted to CLL cases, and should not be applied to lymphocytosis-related conditions. Inappropriate use of this term can cause great anxiety in individuals receiving their blood count results, as well as in their families. In a web search engine commonly used to clear doubts on medical terms, there are countless pages where Gumprecht shadows are associated with CLL.